Kekuasaan Yudisial dalam Sistem Demokrasi Konstitusional: Membangun Antitesis Dekonstitusionalisasi dan Politisasi Peradilan - Sitabuana, Tundjung Herning; Surya Nagara, Airlangga; Sanjaya, Dixon (Jurnal Hukum & Pembangunan, 2026)
Strengthening idea of constitutional democracy as a transitional phase towards a modern rule of law requires one of main characteristics of an independent judiciary. Current phenomena demonstrate how utopian these conditions are as the judiciary becomes increasingly politically pragmatic, transactional, interdependent, and demoralized. At the same time, phenomenon of constitutional defiance is growing stronger with efforts to deconstitutionalize and politicize the judiciary. This study aims to explore the existence and legitimacy of the judiciary in constitutional democracy era against that phenomenon. The research was conducted doctrinally with a historical, conceptual, and comparative approach that was analyzed qualitatively. The results indicate two main issues: (1) the principle of constitutionalism demands the separation of power and checks and balances. The progress of constitutional discourse shows the occurrence of democratic regression where the branches of power contribute to each other, creating damage and a lack of commitment to upholding the supremacy of law. The independent judiciary has failed to carry out its functions and the concept of constitutional democracy isn’t seen as a stable concept unless it is reactive when power returns to its genealogical signs, totalitarianism. The experience of democratic countries shows that this weakening leads to a defective democracy or new despotism; and (2) In the Indonesian context, legal politics and practice of judicial power show that judiciary is always interdependent in all indicators, both internal and external. The concept of an independent judiciary is only realized in a formalistic-normative manner but isn’t realized in real judicial practice. The judiciary and judicial actors can’t avoid being actors and objects of politics in the dynamics of Indonesian state system. Several conceptors are trying to rebuild the discourse of re-democratization as a whole, the institution of trias politica or build a new discourse through discursive constitutionalism with participation of the public as a new determinant that will oversee the implementation of power to act constitutionally.